2003
DOI: 10.1590/s0100-879x2003001200012
|View full text |Cite
|
Sign up to set email alerts
|

The L-arginine/nitric oxide/cyclic-GMP pathway apparently mediates the peripheral antihyperalgesic action of fentanyl in rats

Abstract: There are only a few studies on the molecular mechanisms underlying the peripheral antihyperalgesic effect of opioids. The aim of this study was to investigate the molecular bases of the peripheral antihyperalgesic effect of fentanyl in a model of prostaglandin-induced chemical hyperalgesia. Prostaglandin E 2 (1.4 nmol) injected into one hind paw of male Wistar rats (200-250 g, N = 6 in each experimental or control group) pretreated with indomethacin (2.5 mg/kg) potentiated the nocifensive response to formalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Due to similar changes in f R and V T , each dose of fentanyl produced qualitatively similar changes in V E consisting of rapid and large decreases followed by a recovery period and then a rise to about 50% above pre-injection values. While the ability of opioids, such as morphine, to depress breathing and the mechanisms by which this occurs have been extensively studied ( Lalley, 2008 ; Pattinson, 2008 ; Dahan et al, 2010 ; Pattinson and Wise, 2016 ; Baby et al, 2018 ; Dahan et al, 2018 ; Bateman et al, 2021 ; Baby et al, 2021a ; Baby et al, 2021b ; Ramirez et al, 2021 ), the sites/mechanisms of action by which fentanyl exerts its cardiorespiratory and antinociceptive effects are less well understood ( Laubie et al, 1977 ; Fone and Wilson, 1986 ; Mayer et al, 1989 ; Yamakura et al, 1999 ; Lalley, 2003 ; Maegawa and Tonussi, 2003 ; Griffioen et al, 2004 ; Mastronicola et al, 2004 ; Nikolaishvili et al, 2004 ; Hajiha et al, 2009 ; Tschirhart et al, 2019 ; Webster and Rauck, 2021 ; Ramos-Matos et al, 2022 ). Mechanisms of action of fentanyl involve activation of μ-ORs in brainstem nuclei controlling cardiorespiratory and nociceptive functions ( Laubie et al, 1977 ; Fone and Wilson, 1986 ; Lalley, 2003 ; Griffioen et al, 2004 ; Nikolaishvili, et al, 2004 ; Hajiha, et al, 2009 ; Webster and Rauck, 2021 ; Ramos-Matos et al, 2022 ), and in peripheral structures, including the carotid body ( Mayer et al, 1989 ; Henderson et al, 2014 ; Tschirhart et al, 2019 ; Ramos-Matos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to similar changes in f R and V T , each dose of fentanyl produced qualitatively similar changes in V E consisting of rapid and large decreases followed by a recovery period and then a rise to about 50% above pre-injection values. While the ability of opioids, such as morphine, to depress breathing and the mechanisms by which this occurs have been extensively studied ( Lalley, 2008 ; Pattinson, 2008 ; Dahan et al, 2010 ; Pattinson and Wise, 2016 ; Baby et al, 2018 ; Dahan et al, 2018 ; Bateman et al, 2021 ; Baby et al, 2021a ; Baby et al, 2021b ; Ramirez et al, 2021 ), the sites/mechanisms of action by which fentanyl exerts its cardiorespiratory and antinociceptive effects are less well understood ( Laubie et al, 1977 ; Fone and Wilson, 1986 ; Mayer et al, 1989 ; Yamakura et al, 1999 ; Lalley, 2003 ; Maegawa and Tonussi, 2003 ; Griffioen et al, 2004 ; Mastronicola et al, 2004 ; Nikolaishvili et al, 2004 ; Hajiha et al, 2009 ; Tschirhart et al, 2019 ; Webster and Rauck, 2021 ; Ramos-Matos et al, 2022 ). Mechanisms of action of fentanyl involve activation of μ-ORs in brainstem nuclei controlling cardiorespiratory and nociceptive functions ( Laubie et al, 1977 ; Fone and Wilson, 1986 ; Lalley, 2003 ; Griffioen et al, 2004 ; Nikolaishvili, et al, 2004 ; Hajiha, et al, 2009 ; Webster and Rauck, 2021 ; Ramos-Matos et al, 2022 ), and in peripheral structures, including the carotid body ( Mayer et al, 1989 ; Henderson et al, 2014 ; Tschirhart et al, 2019 ; Ramos-Matos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of nitrosyl factors, such as NO and SNOs, in the pharmacological actions of opioids has received considerable attention. For example, there is substantial evidence for nitrosyl factors playing roles in 1) opioid receptor (OR) signaling processes ( Pol, 2007 ; Toda et al, 2009a ; Toda et al, 2009b ; Rodríguez-Muñoz and Garzón, 2013 ), and 2) opioid effects on a) vascular function and reactivity ( Sahin et al, 2005 ; Kaye et al, 2006 ), b) pain processing ( Pelligrino, et al, 1996 ; Maegawa and Tonussi, 2003 ; Cury et al, 2011 ; Hervera et al, 2011 ; Mehanna et al, 2018 ; Ortiz et al, 2020 ), c) vision ( Someya et al, 2017 ), and d) inflammatory-immunoregulatory processes ( Bilfinger, et al, 1998 ; Jan et al, 2011 ). Additionally, nitrosyl factors are involved in opioid-induced catalepsy ( Erkent et al, 2006 ), tolerance to opioids ( Kissin et al, 2000 ; Ozdemir et al, 2011 ; Durmus et al, 2014 ), and fentanyl pre-conditioning ( Lu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the L-arginine/NO/cGMP pathway has an important role in peripheral antinociception induced by opioids. Peripheral antinociceptive effect induced by a μ-opioid receptor agonists morphine (Ferreira et al 1991) and fentanyl (Maegawa and Tonussi 2003) was inhibited by enzymatic NO biosynthesis blockers and by a guanylate cyclase inhibitor, specific cyclic GMP phosphodiesterase inhibitor. Furthermore, peripheral antinociception induced by κ-and δ-opioid receptor activation seems to be mediated by the NO/cGMP pathway (Amarante and Duarte 2002;Pacheco et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The NO/cGMP/ATP-sensitive K + channel pathway is one of the mechanism of action of some analgesics such as diclofenac and fentanyl. [4][5][6] However, according to our test results, the peripheral antinociceptive action of PCA involved another NO related pain pathway, not NO-cGMP-ATP sensitive K + channels pathway. The other possible NO related pain pathway involvement in PCA antinociception is still under investigation.…”
Section: Involvement Of Atp-sensitive K + Channel Pathwaymentioning
confidence: 66%
“…In vivo pharmacological studies imply that ATP-sensitive K + channels in peripheral sensory neurons may be activated indirectly via the NO/cGMP/ PKG pathway and this pathway is one of the mechanism of action for various analgesic drugs such as diclofenac and fentanyl. [4][5][6] The acetic acid induced writing test is one of the most commonly used methods for measuring peripheral analgesic activity in mice. 7 Previously, in another study, 8 we found that 150 and 300 mg/kg (p.o.)…”
Section: Introductionmentioning
confidence: 99%